Faktor-Faktor yang Mempengaruhi Tingkat Kemiskinan di Mojokerto - Nabiilah Faadiyah Putut; Niniek Imaningsih; Riko Setya Wijaya (Al-Buhuts, 2021)
This study aims to determine how much influence the minimum wage, unemployment, and education have on poverty in Mojokerto. The data used in this study are scaled data for 10 years (time series) from 2010-2019, this data is taken from the Central Statistics Agency (BPS). To determine the magnitude of the influence of an independent variable on the dependent variable, this study uses a multiple linear regression model using the SPSS software application. The results of this study simultaneously Minimum Wage, Unemployment, and Education affect the Poverty Level in Mojokerto City. While individually it is the Minimum Wage variable that affects the Poverty Level in Mojokerto City. This happens, because basically, poverty is the impact of development that is less focused on social aspects. Poverty, unemployment, education, minimum wages